Cobalt Resistance via Detoxification and Mineralization in the Iron-Reducing Bacterium Geobacter sulfurreducens - Dulay, Hunter; Tabares, Marcela; Kashefi, Kazem; Reguera, Gemma (Frontiers in Microbiology, 2020)
Bacteria in the genus Geobacter thrive in iron- and manganese-rich environments where the divalent cobalt cation (CoII) accumulates to potentially toxic concentrations. Consistent with selective pressure from environmental exposure, the model laboratory representative Geobacter sulfurreducens grew with CoCl2 concentrations (1 mM) typically used to enrich for metal-resistant bacteria from contaminated sites. We reconstructed from genomic data canonical pathways for CoII import and assimilation into cofactors (cobamides) that support the growth of numerous syntrophic partners. We also identified several metal efflux pumps, including one that was specifically upregulated by CoII. Cells acclimated to metal stress by downregulating non-essential proteins with metals and thiol groups that CoII preferentially targets. They also activated sensory and regulatory proteins involved in detoxification as well as pathways for protein and DNA repair. In addition, G. sulfurreducens upregulated respiratory chains that could have contributed to the reductive mineralization of the metal on the cell surface. Transcriptomic evidence also revealed pathways for cell envelope modification that increased metal resistance and promoted cell-cell aggregation and biofilm formation in stationary phase. These complex adaptive responses confer on Geobacter a competitive advantage for growth in metal-rich environments that are essential to the sustainability of cobamide-dependent microbiomes and the sequestration of the metal in hitherto unknown biomineralization reactions.